Raising rural women's voices: From self-silencing to self-expression. (2nd November 2017) - Bogar, Sandra; Ganos, Emmy; Hoormann, Kelly; Bub-Standal, Caryn; Beyer, Kirsten M. M.
ABSTRACT: Within the context of a community-academic partnership, we undertook a mixed-methods study to identify and explore health status, priorities, and management strategies among aging Wisconsin rural women. A questionnaire measuring diverse wellness needs was administered to women participating in personal development programming offered by a rural nonprofit organization. A subgroup participated in qualitative interviews to deepen the understanding of identified health priorities and methods of coping and healing. Findings provide insight into the prevalence of self-silencing among rural women and highlight mechanisms that help to facilitate the dismantling of self-silencing.